Development of an All Solid State Battery Incorporating Graphene Oxide as Proton Conductor. Issue 6 (1st August 2017) - Shudo, Yuta; Islam, Md. Saidul; Karim, Mohammad Razaul; Rabin, Nurun Nahar; Wakata, Kosuke; Ohtani, Ryo; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : All solid state battery is fabricated by incorporating graphene oxide electrolyte. Respective discharge capacity and power density of the cell is found to be 360 μAh and 19.5 mW kg −1 at a constant current drain of 3 μA. Abstract : Graphene oxide (GO) shows high proton conductivity (≈10 −4 Scm −1 ), excellent mechanical stability, and electrical insulation property, which makes it an ideal candidate for use as a proton conducting solid state electrolyte. The prospects of using GO as single phase solid electrolyte in an all solid battery is presented herein. A battery with the cell configuration: Zn + ZnSO4 7H2 O + graphite (anode) || GO (electrolyte) || MnO2 + graphite (cathode) is fabricated. Cyclic voltammetry confirms its rechargeable nature. The respective discharge capacity and power density of the cell are 360 μAh and 19.5 mW kg −1 at a constant current drain of 3 μA under the experimental conditions employed. GO based proton conductors are cleaner and cheaper than other solid electrolytes. The current study strongly suggests that GO can be used as a practical and beneficial component in solid state battery applications with low energy feedback.